Pengaruh Perputaran Modal Kerja, Perputaran Aset Tetap, Rasio Lancar dan Pertumbuhan Penjualan terhadap Net Profit Margin - Marpaung, Bintang Sahala; Hasibuan, David M.H.; Magdalena, Annaria; Khoirunnisa, Aina Rizky (PT. Karya Inovatif Nusantara, 2024)
This study aims to determine the Effect of Working Capital Turnover, Fixed Asset Turnover, Current Ratio and Sales Growth on Net Profit Margin. The problem of this research is whether Working Capital Turnover, Fixed Asset Turnover, Current Ratio and Sales Growth have a positive effect on Net Profit Margin. The type of research used is a quantitative method with a classical assumption test consisting of a normality test, heteroscedasticity test, multicollinearity test and autocorrelation test. The research sample is as many as 15 companies, and the data collected is secondary data. The Analysis Model uses multiple linear regression tests consisting of t test, f test and determinant coefficient test. The results of this study show that working capital turnover has a negative and significant effect on net profit margin, fixed asset turnover has a negative and significant effect on net profit margin, current ratio has no effect on net profit margin, sales growth does not affect net profit margin, and simultaneously the variables Working Capital Turnover, Fixed Asset Turnover, Current Ratio and Sales Growth have a positive and significant effect on net profit Margin.